Comparison of two different rectal spacers in prostate cancer external beam radiotherapy in terms of rectal sparing and volume consistency. Issue 2 (August 2015) - Wolf, Frank; Gaisberger, Christoph; Ziegler, Ingrid; Krenn, Elisabeth; Scherer, Philipp; Hruby, Stephan; Schätz, Tobias; Forstner, Rosemarie; Holzinger, Josef; Vaszi, Andrea; Kametriser, Gerhard; Steininger, Philipp; et al.
Abstract Background and purpose In external beam radiation (EBRT) of the prostate, the rectum is the dose-limiting organ at risk, and sparing of the anterior rectal wall is a prerequisite for safe delivery of doses beyond 70 Gy. Spatial sparing of the rectum can be achieved by introducing a spacer material into the retroprostatic space, thus separating the anterior rectal wall from the PTV. Materials and methods Two spacer technologies, Spacer OAR, a polyethylene glycol gel and ProSpace, a saline inflated balloon, were compared in terms of spacer volume, stability, and dose reduction to the anterior rectum wall in 78 patients. Results Both spacer systems significantly reduced the rectum surface encompassed by the 95% isodose (gel: −35%, p < 0.01; balloon −63.4%, p < 0.001) compared to a control group. The balloon spacer was superior in reducing rectum dose (−27.7%, p = 0.034), but exhibited an average volume loss of >50% during the full course of treatment of 37–40 fractions, while the volume of gel spacers remained fairly constant. Conclusions In choosing between the two spacer technologies, the advantageous dose reduction of the balloon needs to be weighed up against the better volume consistency of the gel spacer with respect to the duration of hypofractionated vs normofractionated regimens.